Studi Komparasi Antara Teori Victor Frankl, Ester Ahn Kim Dan Elisabeth Kubler-Ross Tentang Kematian Bagi Konstruksi Pendampingan Pastoral - Tombeng, Ineke Marlien (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
This research aims to investigate the embodiment of people who facing the death, from the perspective of Victor Frankl, Ester Ahn Kim, and Kubler-Ross. The psychological symptoms from the people who facing the death is more affected by time, according to Frankl. How long the endurance last giving impact to the emergence of psychic change and triggering of certain attitudes and behaviors making. They had moral advancement or become religious. It shows that in the drawback situation, there are many pressures and torments, and the death threat, people can still act differently, not just giving up to the influence of environment which could lead to psychic deformation or primitiveness. Ester Ahn Kim research about people (Korean prisoners from Japan’s colony) who facing the death and showing the fear reaction. The fear is not only about facing the death, but also because the persecution and suffering that they had.Elizabeth Kubler-Ross also talk about the attitude of people who facing the death, with the emphasize to the terminal illness patients, or to they who seriously ill. There are five bold phases to the characteristics of people toward their death, which is rejection or denial, angry, bargaining, depression, and accepting. The rejection shows that there is a fear. In pastoral counseling, finding the solution together for the problem they had. The attempt to help the other is a holistic help, which is physically and spiritually that driven by the will to do the good things to accept the presence of God.